Characterization of Electronic and Ionic Transport in Li1-xNi0.33Mn0.33Co0.33O2 (NMC333) and Li1-xNi0.50Mn0.20Co0.30O2 (NMC523) as a Function of Li Content. Issue 8 (13th May 2016) - Amin, Ruhul; Chiang, Yet-Ming
Abstract : Despite the extensive commercial use of Li1- x Ni1-y-z Mnz Coy O2 (NMC) as the positive electrode in Li-ion batteries, and its long research history, its fundamental transport properties are poorly understood. These properties are crucial for designing high energy density and high power Li-ion batteries. Here, the transport properties of NMC333 and NMC523 are investigated using impedance spectroscopy and DC polarization and depolarization techniques. The electronic conductivity is found to increase with decreasing Li-content (increasing state-of-charge) from ∼10 −7 Scm −1 to ∼10 −2 Scm −1 over Li concentrations x = 0.00 to 0.75, corresponding to an upper charge voltage of 4.8 V with respect to Li/Li + . The lithium ion diffusivity is at least one order of magnitude lower, and decreases with increasing x to at x = ∼0.5. The ionic conductivity and diffusivity obtained from the two measurements techniques (EIS and DC) are in good agreement, and chemical diffusion is limited by lithium transport over a wide state-of-charge range.